Peran Harta Perspektif Ekonomi Islam Dalam Era Pandemi Covid-19 - Habib Masyhudi (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2021)
Abstrak: Since the beginning of March 2020, Indonesia has faced a major epidemic that has haunted the world, namely the corona virus (covid-19) which of course has an impact on the global economy. This research was conducted with the aim of presenting the concept of wealth from an Islamic economic perspective and its role in the Covid-19 pandemic era. The results showed that the acquisition, management and use of assets must be in accordance with sharia. This concept indicates that there are binding rules in every human behaviour in treating his property. Because of in Islam, in the afterlife, people will be held accountable for their assets. Therefore, it is necessary to pay attention to the principles and principles of sharia in empowering the assets owned. Furthermore, Islamic social finance has an important potential in overcoming the global socio-economic problems of the impact of covid-19. Indonesia as a country with the largest Muslim majority can maximize the potential of Islamic social funds. There are two main tasks that can be done to fight the Covid-19 pandemic, namely prevention and solution measures. Empowerment of Islamic social funds can be maximized to help people survive. Kata Kunci : Harta, Ekonomi Islam, Pandemi Covid-19